The Human Genome Project : cracking the code within us - Marshall, Elizabeth L. (New York : F. Watts, 1996)
Describes the ten-year, multimillion dollar Human Genome Project and its process of gene mapping and addresses some of the criticisms of the project.
Includes bibliographical references (p. 119-120) and index.
Booklist.
School Library Journal.
Wilson's Senior High School.
Young Adult
Keywords: Human Genome Project; Human Genome Project; Human Genome Project; Gene mapping; Genetics; Genomes; Gene mapping; Genetics; Genomes; Gene mapping; Genetics